Aspiring Gender in BRICS: Institutionalising Gender Aspirations of the Global South through BRICS Feminist Watch (BFW) - Nursabrina Rahmawati (Global South Review, 2026)
BRICS Feminist Watch (BFW), a transnational feminist alliance, channels and institutionalizes alternative gender norms rooted in Global South experiences into the BRICS framework, aiming for a more inclusive and gender-just global order. While BRICS, as a strategic bloc in a post-hegemonic world, pays limited formal attention to gender equality, BFW addresses this gap by advancing justice models distinct from the mainstream Global North approaches. Functioning as a civil society organization (CSO), BFW exemplifies the growing influence of non-state actors in global policy advocacy such as mobilizing collective action, shaping discourses, and pressing for economic development agendas that are responsive to gender realities of BRICS societies. Through both formal and informal channels, BFW challenges the dominance of state actors and mainstream paradigms, advocating for greater representation, accountability, and the integration of gender perspectives in BRICS policy-making and development projects. Operating amid diverse ideological contexts and lacking specific institutional mechanisms for gender issues within BRICS, BFW leverages solidarity, expertise, and advocacy networks to contest and revise established norms. The distinctive position of BFW demonstrates how transnational feminist CSOs from the Global South can generate institutional transformation within emerging global governance platforms, offering critical alternatives to prevailing gender and development discourses.